Model Pengasuhan Alternatif Pada Dual-Career Family - Hidayati, Laily (PROGRAM STUDI PENDIDIKAN GURU RAUDLATUL ATHFAL (PGRA) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2016)
This study used a qualitative approach with multi-case studies. Data were taken and analyzed from five (5) cases with special characteristics that are different, but all of them belong to the dual-career family, or the familys mother and father are both working outside the home, and choose to transfer the responsibilities of child care to second hand that is baby sitter or we used to call ânannyâ. Families as respondents in this study include couples who work as both a teacher there who work as self-employed and teachers, there is work as village officials and teachers, some are working as doctors and employees of the company, there is also a religious affairs office workers and teachers. Data obtained by using observation and interview. This study aims to gain an overview of alternative care models in dual-career families, the family in which the father and mother both work outside the home and profession specific jobs, so that child care is delegated to a third party for working parents. Researchers restrict research on the subject with the criteria of dual-career who have children aged 0-8 years, otherwise known as early childhood. Parenting is pointing in a certain way that is done by parents in meeting the basic needs of a child, that needs sharpening, compassion, and parenting. The results of this study are expected to be additional colors in theoretical construct of parenting in accordance with the characteristics of families in Tuban and Indonesia in general.